ANALISIS HUBUNGAN ANTARA INDIKATOR PENDIDIKAN DAN KINERJA PEREKONOMIAN DI INDONESIA - Chitra Indah Yuliana (Widyariset, 2009)
This research aims to investigate relationship between education indicator represented by literacy rate and Gross Domestic Product (GDP) real per capita as economic performance with annual data during period of 1980 until 2008 in Indonesia. The analysis method used in this research was Vector Auto Regression (VAR) with Granger Causality Test, Impulse Responses, and Variance Decomposition. In addition, Akaike and Schwarz Information Criterion determined optimum lag of 6 that could be estimated. Granger causality test showed literacy rate significantly Granger-caused GDP real per capita, but there was no significant Granger causality from GDP real per capita to literacy rate over research period. One of crucial implications of this research results is that we must and still need to make the highest priority of base education development especiallyliterate promotion so that high level of economic performance could be equally generated in improving the prosperity of Indonesian societies.